PRICE THE MAIN CONDITION FOR COFFEE EXPORTS AN ANALYSIS WITH GOOD NEWS AND BAD NEWS APPROACHES IN INDONESIA - Anwar, Khairil; Mariyudi, Mariyudi (CV. Radja Publika, 2021)
This study aims to analyze the effect of prices and income of the United States of America on 5 superior commodities in Indonesia and see between good news and bad news. The research data uses quarterly data from 2005Q1-2017Q4. The research model uses the TGARCH model. The results show that the income per capita of the United States, the previous price per commodity and previous exports have a positive and significant influence on commodity exports. However, the effect of per capita income on superior rubber commodities was found to have a negative and significant effect. This indicates an increase in foreign income will reduce rubber exports. Extreme volatility shocks occur in palm oil and other agriculture. High volatility is only cocoa commodity. Meanwhile, for coffee and rubber, the volatility is low. 3 commodities that have symmetrical information are coffee, cocoa, and other agriculture. Asymmetric information on palm oil and rubber commodities.